2013
DOI: 10.1002/jez.1781
|View full text |Cite
|
Sign up to set email alerts
|

β‐Endorphin‐induced Inhibition of Vitellogenic Follicular Growth in the Fish Oreochromis mossambicus: Evidence for Opioidergic Mediation of Ovarian Stress Response

Abstract: The opioid peptide β-endorphin (β-EP) is known to play modulatory role in vertebrate reproduction. The objective of the present study was to determine the influence of β-EP and the opioid receptor antagonist naltrexone (NALT) on follicular development in normal, and stressed female tilapia Oreochromis mossambicus. Administration of 4 µg β-EP, but not 0.5 or 1.5 µg β-EP daily for 22 days caused a significant reduction in the mean GSI, HSI, and number of Stage IV (vitellogenic) follicles compared to experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…For instance, opioid peptide β‐endorphin is released in response to stress in the fish gilthead sea bream Sparus aurata (Mosconi et al, ; Arends et al, ). Our previous studies also have suggested a role for the involvement of β‐endorphin in mediation of reproductive stress response as shown by the suppression of LH secretion in the pituitary gland (Ganesh and Chabbi, ) and inhibition of vitellogenic follicular growth (Chabbi and Ganesh, ) in O. mossambicus . Therefore, the possibility of involvement of other inhibitory factors, which might act at the multiple sites of endocrine axis during reproductive stress response, cannot be ruled out for this species.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For instance, opioid peptide β‐endorphin is released in response to stress in the fish gilthead sea bream Sparus aurata (Mosconi et al, ; Arends et al, ). Our previous studies also have suggested a role for the involvement of β‐endorphin in mediation of reproductive stress response as shown by the suppression of LH secretion in the pituitary gland (Ganesh and Chabbi, ) and inhibition of vitellogenic follicular growth (Chabbi and Ganesh, ) in O. mossambicus . Therefore, the possibility of involvement of other inhibitory factors, which might act at the multiple sites of endocrine axis during reproductive stress response, cannot be ruled out for this species.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, treatment of naloxone prior to CRH injection blocked the inhibitory effect of CRH on pulse generator frequency of GnRH in rhesus monkey (Williams et al, ). Indeed, the possibility of opioidergic mediation in suppression of LH content in the pituitary gland (Ganesh and Chabbi, ) and vitellogenic follicular growth in the ovary (Chabbi and Ganesh, ) during reproductive stress response is shown in tilapia. Since the possibility of crossing of adequate CRH through the blood–brain barrier is not clear in the present study, we cannot comment about its centrally mediated effects.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in the progression of vitellogenic follicular growth was also observed following treatment with other opioid peptides such as β‐EP (135 μg kg −1 bw), EM‐1 or EM‐2 (1000 μg kg −1 bw) and leucine enkephalin (7500 μg kg −1 bw) in O. mossambicus (Chabbi & Ganesh, ; Vijayalaxmi & Ganesh, , ). In contrast, a stimulatory effect on stage I follicular development was observed following treatment with 50 μg β‐EP kg −1 bw or 625 and 2500 μg leucine enkephalin kg −1 bw in O. mossambicus (Chabbi & Ganesh, ; Vijayalaxmi & Ganesh, ). In the present study, treatment of 250 μg DYN kg −1 bw did not result in such an increase, but rather caused a significant reduction in the number of stage I follicles compared with those of time‐matched controls.…”
Section: Discussionmentioning
confidence: 96%
“…Endogenous opioid peptides have been shown to be involved in the regulation of several physiological functions, including reproduction, in different vertebrates (Ciarcia et al ., ; Facchinetti et al ., ; Faletti et al ., ; Ganesh & Yajurvedi, ; Leadem & Kalra, ; Olson et al ., ; Polzonetti‐Magni et al ., ; Zerani & Gobbetti, ). Among fishes, treatment with an opioid peptide, β‐endorphin (β‐EP), inhibits the function of the pituitary–ovary axis (Chabbi & Ganesh, ; Ganesh & Chabbi, ), whereas a dose‐dependent stimulatory as well as an inhibitory effect of leucine enkephalin on reproductive axis is demonstrated in the cichlid fish Oreochromis mossambicus (Peters 1852) (Vijayalaxmi & Ganesh, ). Dynorphin is another class of opioid peptide, which is produced from the prodynorphin gene and exists in different forms such as dynorphin‐A (DYN), dynorphin‐B and β‐neoendorphin, among which dynorphin‐A (1–17) is highly conserved and most potent (Civelli et al ., ; James et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a stress hormone of the HPI axis, cortisol, was shown to exert direct inhibitory effect on ovarian steroidogenesis in vitro in rainbow trout O. mykiss . Similarly an opioid peptide, β‐endorphin, which is released in response to stress in fish , was shown to mediate an ovarian stress response in O. mossambicus . Similarly, β‐endorphin caused inhibition of follicle‐stimulating hormone‐induced ovarian recrudescence in the lizard Mabuya carinata and reduced the number of oocytes ovulated after human chorionic gonadotrophin injection in vivo and prevented ovulation in in vitro isolated ovaries of mammals .…”
Section: Discussionmentioning
confidence: 99%